A method for preparing a high-entropy alloy catalyst by explosive explosion
Patent Information
- Application Number
- CN202611043746.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-07-08
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]本发明的目的在于克服现有技术中高熵合金催化剂制备过程中存在的多金属合金化不充分、相分离、颗粒尺寸难以控制以及制备效率较低等缺陷,提供一种炸药爆炸的新高熵合金催化剂制备方法
[0027]1、本发明采用炸药爆炸法制备高熵合金催化剂,爆炸过程能够在微秒时间内实现瞬时超高温升温,并在后续经历快速降温,从而形成超快热合成过程。该过程有利于多种金属前驱体的快速还原、熔融、成核和合金化,并促进多元素在纳米尺度上的充分混合;同时,快速冷却可有效抑制颗粒持续长大和元素偏析,有利于形成粒径较小、分散性较好的高熵合金纳米颗粒。因而,本发明方法在超小尺寸高熵合金催化剂制备方面具有明显优势。
Smart Images

Figure CN122895008A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing high-entropy alloy catalysts by explosive detonation, belonging to the field of high-entropy alloy catalyst preparation. Background Technology
[0002] High-entropy alloys typically refer to multi-element alloy materials composed of five or more metallic elements in equimolar or near-equimolar ratios. Compared to traditional binary or ternary alloy systems, high-entropy alloys, due to their high-entropy effect, lattice distortion effect, hysteresis diffusion effect, and cocktail effect, generally exhibit superior stability, corrosion resistance, and multifunctionality, and have broad application prospects in aerospace, energy catalysis, biomedicine, and other fields.
[0003] Since 2018, high-entropy alloys have attracted widespread attention in the field of catalysis. Because high-entropy alloy catalysts contain multiple metal components, they possess a rich variety of active sites. Furthermore, synergistic effects can occur between different metals, thereby modulating the electronic structure of the catalyst surface, the adsorption energy of catalytic reaction intermediates, and the reaction energy barrier. Therefore, high-entropy alloy catalytic materials have shown good application potential in various catalytic reactions, including hydrogen evolution reaction, oxygen evolution reaction, oxygen reduction reaction, and carbon dioxide reduction reaction.
[0004] However, the preparation of high-entropy alloy catalysts still faces significant challenges. Different metal elements exhibit substantial differences in atomic radius, melting point, and standard reduction potential, easily leading to problems such as elemental segregation, localized enrichment, phase separation, and particle agglomeration during the preparation process. Particularly for high-entropy systems composed of five or more metal components, achieving uniform mixing, simultaneous reduction, and rapid alloying of multi-metal salt precursors within a short timeframe is crucial for obtaining high-entropy alloy catalysts with homogeneous composition and stable structure.
[0005] Existing methods for preparing high-entropy alloy catalysts mainly include mechanical alloying, wet chemical reduction, high-temperature pyrolysis, rapid Joule heating, and laser methods. While these methods can achieve alloying of multiple metal components to a certain extent, they still suffer from limitations in heating and cooling processes, long high-temperature treatment times, easy particle growth, high equipment requirements, or low preparation efficiency. Therefore, it is necessary to develop a new method for preparing high-entropy alloy catalysts to achieve rapid alloying of multiple metal components and effectively suppress elemental segregation and particle agglomeration. Summary of the Invention
[0006] The purpose of this invention is to overcome the defects in the preparation process of high-entropy alloy catalysts in the prior art, such as insufficient multi-metal alloying, phase separation, difficulty in controlling particle size, and low preparation efficiency, and to provide a new method for preparing high-entropy alloy catalysts for explosive detonation.
[0007] The objective of this invention is achieved through the following technical solution:
[0008] This invention discloses a method for preparing high-entropy alloy catalysts by explosive detonation, comprising the following steps:
[0009] Step 1: Carrier preparation: After the carrier precursor is thoroughly mixed and homogeneous, it is calcined at high temperature under an inert atmosphere. The calcined product is then post-treated to obtain the carrier.
[0010] Step 2: Preparation of metal salt precursor solutions: Dissolve different types of metal salt precursors in the same type of solvent to prepare metal salt precursor solutions of the same concentration.
[0011] Step 3, Impregnation and Loading: The carrier obtained in Step 1 is ultrasonically dispersed in a solvent and fully wetted. Then, the different metal salt precursor solutions and explosives obtained in Step 2 are added in proportion. After ultrasonic dispersion and stirring, the carrier is fully impregnated so that the metal salt precursors and explosives are fully loaded on the surface of the carrier. Then, the carrier is dried and ground to obtain the precursor composite powder.
[0012] Step 4, Explosive Synthesis: The precursor composite powder obtained in Step 3 is placed in a ceramic boat, and the ceramic boat is placed in a tube furnace to heat and detonate the explosive in the precursor composite powder in Step 3. The rapid heating and cooling in the high-entropy alloy catalyst synthesis process is achieved through the explosive explosion process. After the explosion, the product is collected, washed, centrifuged and dried to obtain the high-entropy alloy catalyst.
[0013] The carrier precursor mentioned in step one is a mixture of dicyandiamide and pyromellitic acid, with a mass ratio of 5:1 to 10:1.
[0014] The high-temperature calcination temperature mentioned in step one is 500–900 °C.
[0015] The metal salt precursors mentioned in step two include acetylacetone salts, nitrates, acetates, sulfates, and chlorides.
[0016] The concentration of the different metal salt precursor solutions in step two is 0.01 mol / L to 0.05 mol / L.
[0017] The ratio described in step three is as follows: the amount of metal salt precursor solution, carrier and explosive is 1~10 mL: 1~200 mg: 1~50 mg; the volume of each metal salt precursor solution is the same.
[0018] The explosives mentioned in step three include TNT, HMX, RDX, TATB, and 5-NAT.
[0019] The detonation temperature of the explosives described in step four is 200–350°C.
[0020] This invention utilizes explosive detonation to prepare high-entropy alloy catalysts, which is significantly different from the slow heating and cooling processes in conventional heating methods. The explosive detonation process is divided into (1) a transient heating process, in which the explosive releases energy in microseconds, and the resulting ultra-high temperature provides conditions for the rapid reaction of various metal salt precursors, promoting the rapid reduction of various metal salt precursors into metal atoms and rapid nucleation and alloying in a short time; (2) a rapid cooling process, which inhibits further particle aggregation and phase separation, and helps to obtain high-entropy alloy catalysts with smaller particle size and uniform distribution.
[0021] Preferably, in step one, the heating rate of the calcination process is 5-10 °C / min, and the calcination atmosphere is a nitrogen atmosphere.
[0022] Preferably, in step two, the metal salt includes five or more of the following: Mn, Fe, Co, Ni, Cu, Pt, Pd, Ir, Ru, and Mo.
[0023] Preferably, in step three, the stirring and impregnation time is 0.1 to 2 days, the drying temperature is 40 to 100 ℃, and the drying time is 1 to 3 days.
[0024] The present invention also provides the application of the high-entropy alloy catalyst obtained by the above preparation method in proton exchange membrane fuel cells.
[0025] Preferably, the high-entropy alloy catalyst is used in the electrode catalyst layer of a proton exchange membrane fuel cell as a cathode oxygen reduction reaction catalyst.
[0026] Beneficial effects:
[0027] 1. This invention employs an explosive detonation method to prepare high-entropy alloy catalysts. The detonation process achieves instantaneous ultra-high temperature rise within microseconds, followed by rapid cooling, thus forming an ultrafast thermal synthesis process. This process facilitates the rapid reduction, melting, nucleation, and alloying of various metal precursors and promotes thorough mixing of multiple elements at the nanoscale. Simultaneously, rapid cooling effectively inhibits continuous particle growth and elemental segregation, which is beneficial for forming high-entropy alloy nanoparticles with smaller particle size and better dispersibility. Therefore, the method of this invention has significant advantages in the preparation of ultra-small high-entropy alloy catalysts.
[0028] 2. In this invention, the concentration of each metal salt precursor solution is the same. By controlling the concentration and addition volume of each precursor solution, multiple metal elements can form a preset feeding ratio during the precursor loading stage, thereby achieving the control of the target morphology and composition. This is beneficial for obtaining a high-entropy alloy nanoparticle catalyst with a composition close to the design ratio.
[0029] 3. This invention is applicable to various high-entropy alloy catalyst systems such as octagonal, nonaionic, and decaionic catalysts. The metal composition is adjustable, and the method has good universality and scalability.
[0030] 4. The deca-element high-entropy alloy catalyst prepared by the method of the present invention exhibits good fuel cell output performance after being assembled into a membrane electrode and tested in a single cell. Attached Figure Description
[0031] Figure 1 A schematic diagram of the temperature-time process of the explosion method of this invention and the conventional heat treatment method;
[0032] Figure 2 The powder X-ray diffraction pattern of the deca-element high-entropy alloy catalyst obtained in Example 1;
[0033] Figure 3 This is a transmission electron microscope image of the deca-element high-entropy alloy catalyst obtained in Example 1;
[0034] Figure 4 The particle size distribution diagram is shown for the deca-element high-entropy alloy catalyst obtained in Example 1.
[0035] Figure 5 The image shows the spherical aberration corrected HAADF-STEM image of a single deca-element high-entropy alloy particle obtained in Example 1.
[0036] Figure 6 The results of inductively coupled plasma (ICP) testing of the deca-element high-entropy alloy catalyst obtained in Example 1 are shown.
[0037] Figure 7 The image shows the performance of the proton exchange membrane fuel cell based on the deca-entropy alloy catalyst obtained in Example 1. Detailed Implementation
[0038] To better illustrate the purpose and advantages of the present invention, the invention will be further described below in conjunction with the accompanying drawings and examples.
[0039] Example 1
[0040] A method for preparing a deca-element high-entropy alloy catalyst, the method comprising the following steps:
[0041] (1) Weigh 1.0 g of dicyandiamide and 0.1 g of pyromellitic acid solid powder, grind and mix them thoroughly, and place them in a tube furnace for high-temperature calcination under N2 atmosphere. The heating rate during calcination was set to 5 ℃ / min, and the temperature was raised to 900 ℃ and held for 120 min. After calcination, the solid was naturally cooled to room temperature, and the obtained solid was taken out, ground thoroughly, washed with alcohol, centrifuged three times, and dried to obtain a black powdery carbon-based support;
[0042] (2) Weigh out 75.95 mg of manganese acetylacetone, 105.95 mg of iron acetylacetone, 77.15 mg of cobalt acetylacetone, 77.07 mg of nickel acetylacetone, 78.53 mg of copper acetylacetone, 117.99 mg of platinum acetylacetone, 91.39 mg of palladium acetylacetone, 146.86 mg of iridium acetylacetone, 119.52 mg of ruthenium acetylacetone, and 97.85 mg of molybdenum acetylacetone respectively, and add them to 30 mL of a mixed solvent of methanol and dichloromethane. Dissolve them evenly by sonication to obtain acetylacetone metal salt precursor solutions with a concentration of 0.01 mol / L.
[0043] (3) Weigh 100 mg of the black powder carrier obtained in step (1), add it to 10 mL of methanol to fully impregnate it, and then ultrasonically disperse it for 20 min. Then add 5 mL of each of the ten metal salt precursor solutions obtained in step (2), and then add 10 mg of explosive (5-nitraminetetrazole), continue to ultrasonically disperse for 20 min, and then stir for 12 h to fully impregnate and load each metal salt precursor and explosive onto the carrier. After impregnation, place the mixture in a 60 ℃ oven to dry for 24 h, and then grind it thoroughly to obtain the precursor composite powder;
[0044] (4) Preheat the tubular furnace to 200 °C, place the precursor composite powder obtained in step (3) in a ceramic boat, and send it into the tubular furnace for heating and detonation. After the explosion reaction is completed, collect the obtained solid product, and after alcohol washing, centrifugation and drying, obtain a deca-element high-entropy alloy catalyst.
[0045] The product obtained in Example 1 was characterized by powder XRD, such as... Figure 2 As shown, the results indicate that the obtained product has the characteristic diffraction peaks of a single solid solution alloy phase, and no obvious diffraction peaks of individual metal phases or metal oxide impurities were observed, indicating that the multi-metal components have been effectively alloyed to form a single-phase solid solution.
[0046] The obtained product was characterized by TEM and its particle size distribution was statistically analyzed, such as... Figure 3 , Figure 4 and Figure 5 As shown, the results demonstrate the successful synthesis of the desired deca-element high-entropy alloy nanoparticles. The particle size distribution diagram indicates that the particles are relatively uniform in size, with an average particle size below 2 nm, classifying them as sub-nanometer-scale high-entropy alloy particles. Elemental surface distribution analysis of the obtained products shows that Mn, Fe, Co, Ni, Cu, Pt, Pd, Ir, Ru, and Mo are uniformly distributed within the nanoparticles, with no obvious elemental segregation or phase separation observed.
[0047] The obtained product was subjected to ICP testing, such as... Figure 6As shown, the results indicate that all metal elements were successfully introduced into the obtained catalyst, and the actual composition basically corresponds to the designed feed ratio.
[0048] Example 2
[0049] A method for preparing a deca-element high-entropy alloy catalyst, the method comprising the following steps:
[0050] This embodiment is basically the same as Example 1, except that the concentration of the acetylacetone metal salt precursor solution prepared in step (2) is 0.05 mol / L. The particle size distribution of the final nanoparticle catalyst obtained in this embodiment was statistically analyzed, and its average particle size was further extended to 5 nm.
[0051] Example 3
[0052] A method for preparing a deca-element high-entropy alloy catalyst, the method comprising the following steps:
[0053] This embodiment is basically the same as that of embodiment 1, except that in step (2), a portion of the metal salts are selected to prepare their precursor solutions. Specifically, 75.30 mg of manganese(II) nitrate tetrahydrate, 121.20 mg of ferric(III) nitrate nonahydrate, 87.31 mg of cobalt(II) nitrate hexahydrate, 87.24 mg of nickel(II) nitrate hexahydrate, 72.48 mg of copper(II) nitrate trihydrate, and 79.94 mg of palladium(II) nitrate dihydrate are weighed and added to 30 mL of the corresponding alcohols, water, or other good solvents. The solutions are then sonicated to dissolve the solutions evenly, resulting in metal salt precursor solutions with a concentration of 0.01 mol / L.
[0054] Example 4
[0055] A method for preparing a deca-element high-entropy alloy catalyst, the method comprising the following steps:
[0056] This embodiment is basically the same as Example 1, except that in step (2), a portion of the metal salts are selected to prepare their precursor solutions using metal chlorides. Specifically, 59.37 mg of manganese chloride tetrahydrate, 81.09 mg of ferric chloride hexahydrate, 71.38 mg of cobalt chloride hexahydrate, 71.31 mg of nickel chloride hexahydrate, 51.14 mg of copper chloride dihydrate, 155.37 mg of chloroplatinic acid hexahydrate, 53.20 mg of palladium chloride, 89.57 mg of anhydrous iridium chloride, and 78.44 mg of ruthenium chloride trihydrate are weighed and added to 30 mL of the corresponding alcohols, water, or other good solvents. The metal salts are then sonicated to fully dissolve them, resulting in metal chloride precursor solutions with a concentration of 0.01 mol / L.
[0057] Example 5
[0058] A method for preparing a nine-element high-entropy alloy catalyst, the method comprising the following steps:
[0059] This embodiment is basically the same as Embodiment 1, except that in step (2), acetylacetonate molybdenum is not used as a metal salt precursor. Instead, acetylacetonate precursor solutions of nine metals, namely Mn, Fe, Co, Ni, Cu, Pt, Pd, Ir and Ru, are prepared. The concentration of each metal salt precursor solution is 0.01 mol / L.
[0060] In step (3), 5.5 mL of each of the nine metal salt precursor solutions were added. The amounts of other carriers, explosives, ultrasonic dispersion conditions, stirring and impregnation conditions, drying conditions, and detonation conditions in step (4) were the same as in Example 1. After the reaction was completed, the catalyst was collected, washed with alcohol, centrifuged, and dried to obtain the nine-element high-entropy alloy catalyst.
[0061] Example 6
[0062] A method for preparing an octagonal high-entropy alloy catalyst, the method comprising the following steps:
[0063] This embodiment is basically the same as Example 1, except that in step (2), manganese acetylacetonate and molybdenum acetylacetonate are not used as metal salt precursors. Instead, acetylacetonate precursor solutions of eight metals, namely Fe, Co, Ni, Cu, Pt, Pd, Ir and Ru, are prepared. The concentration of each metal salt precursor solution is 0.01 mol / L.
[0064] In step (3), 6 mL of each of the eight metal salt precursor solutions were added. The amounts of other carriers, explosives, ultrasonic dispersion conditions, stirring and impregnation conditions, drying conditions, and detonation conditions in step (4) were the same as in Example 1. After the reaction was completed, the catalyst was collected, washed with alcohol, centrifuged, and dried to obtain an octagonal high-entropy alloy catalyst.
[0065] Example 7
[0066] Application of deca-entropy alloy catalysts in proton exchange membrane fuel cells.
[0067] In some embodiments, the deca-entropy alloy catalyst from Example 1 is mixed with a polymer dispersion and a solvent to prepare a cathode catalyst slurry, which is then uniformly sprayed or coated onto the surface of the gas diffusion layer and dried to form a cathode catalyst layer. A commercially available Pt / C catalyst is used as the anode, and its catalyst layer is prepared in a similar manner. Subsequently, the cathode catalyst layer, anode catalyst layer, and proton exchange membrane are assembled to form a membrane electrode assembly (MEA), which is further assembled into a single-cell test fixture with a flow field plate and a sealing structure to construct a proton exchange membrane fuel cell single cell. After assembly, the single cell is connected to a fuel supply and testing system, and hydrogen is introduced to the anode and oxygen to the cathode for fuel cell performance testing. The anode and cathode temperatures are both controlled at 80 °C, the cathode relative humidity is 100%, and the back pressure is 2.0 bar.
[0068] like Figure 7 The polarization and power density curves show that, under H2-O2 conditions, the single cell achieves a current density of 2.22 A cm⁻¹ at 0.62 V. -2 The maximum power density reaches 2.14 W / cm². -2 The above test results indicate that the high-entropy alloy catalyst prepared by the method of this invention has good application potential as a proton exchange membrane fuel cell cathode.
[0069] It should be noted that the application of proton exchange membrane fuel cells is only one example of the performance verification and application of the high-entropy alloy catalyst obtained in this invention, and does not constitute a limitation on the scope of application of this invention. The high-entropy alloy catalyst prepared according to the method of this invention can also be applied to various catalytic fields such as hydrogen evolution reaction, oxygen evolution reaction, and carbon dioxide reduction reaction.
[0070] This application utilizes the instantaneous high temperature generated by explosive detonation to achieve rapid reduction and alloying of polymetallic salt precursors, which can effectively solve the problem of insufficient alloying of polymetallic components in traditional preparation methods.
[0071] The rapid cooling process following the explosion of the explosive in this application helps to suppress further particle growth and phase separation, thereby obtaining a high-entropy alloy nanoparticle catalyst with smaller particle size and better dispersibility.
[0072] The product obtained in this application has been characterized by XRD, ICP, TEM and HAADF-STEM, which have shown that it has the characteristics of forming a high-entropy alloy structure.
[0073] The method described in this application is applicable to high-entropy alloy systems with different numbers of metal components, and has good universality and scalability.
[0074] The high-entropy alloy catalyst prepared in this application showed good application performance in the single-cell test of proton exchange membrane fuel cell, indicating that the method of this invention can not only achieve efficient synthesis of high-entropy alloy catalyst, but also endow the obtained material with practical application value.
[0075] The above detailed description further illustrates the purpose, technical solution, and beneficial effects of the invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing high-entropy alloy catalysts by explosive detonation, characterized in that: Includes the following steps, Step 1, Carrier Preparation: After the carrier precursor is thoroughly mixed and homogeneous, it is calcined at high temperature under an inert atmosphere. The calcined product is then post-treated to obtain the carrier. Step 2: Preparation of metal salt precursor solutions: Dissolve different types of metal salt precursors in the same type of solvent to prepare metal salt precursor solutions of the same concentration. Step 3, Impregnation and Loading: The carrier obtained in Step 1 is ultrasonically dispersed in a solvent and fully wetted. Then, the different metal salt precursor solutions and explosives obtained in Step 2 are added in proportion. After ultrasonic dispersion and stirring, the carrier is fully impregnated so that the metal salt precursors and explosives are fully loaded on the surface of the carrier. After drying and grinding, the precursor composite powder is obtained. Step 4, Explosive Synthesis: The precursor composite powder obtained in Step 3 is placed in a ceramic boat, and the ceramic boat is placed in a tube furnace to heat and detonate the explosive in the precursor composite powder in Step 3. The rapid heating and cooling in the high-entropy alloy catalyst synthesis process is achieved through the explosive explosion process. After the explosion, the product is collected, washed, centrifuged and dried to obtain the high-entropy alloy catalyst.
2. The method as described in claim 1, characterized in that: The carrier precursor mentioned in step one is a mixture of dicyandiamide and pyromellitic acid, with a mass ratio of 5:1 to 10:
1.
3. The method as described in claim 1, characterized in that: The high temperature mentioned in step one refers to a temperature of 500–900 ℃.
4. The method as described in claim 1, characterized in that: The metal salt precursors mentioned in step two include acetylacetone salts, nitrates, acetates, sulfates, and chlorides.
5. The method as described in claim 1, characterized in that: The concentration of the different metal salt precursor solutions in step two is 0.01 mol / L to 0.05 mol / L.
6. The method as described in claim 1, characterized in that: The ratio described in step three is as follows: the amount of metal salt precursor solution, carrier and explosive is 1-10 mL: 1-200 mg: 1-50 mg; the volume of each metal salt precursor solution is the same.
7. The method as described in claim 1, characterized in that: The explosives mentioned in step three include TNT, HMX, RDX, TATB, and 5-NAT.
8. The method as described in claim 1, characterized in that: The detonation temperature of the explosives described in step four is 200–350 °C.
9. The method as described in claim 1, characterized in that: In step one, the heating rate of the calcination process is 5-10 °C / min, and the calcination atmosphere is a nitrogen atmosphere; In step two, the metal salt includes five or more of the following: Mn, Fe, Co, Ni, Cu, Pt, Pd, Ir, Ru, and Mo. In step three, the stirring and soaking time is 0.1 to 2 days, the drying temperature is 40 to 100 ℃, and the drying time is 1 to 3 days.
10. The high-entropy alloy catalyst prepared by any one of claims 1 to 8, characterized in that: The high-entropy alloy catalyst is used in the electrode catalyst layer of a proton exchange membrane fuel cell as a cathode oxygen reduction reaction catalyst.